2019
DOI: 10.1136/tsaco-2018-000272
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustion of the immune system by Group A Streptococcus necrotizing fasciitis: the occurrence of late secondary infections in a retrospective study

Abstract: BackgroundNecrotizing fasciitis is a potentially lethal condition for which early and adequate treatment with surgical debridement and broad-spectrum intravenous antibiotics are essential for survival. It is hypothesized that Group A Streptococcus (GAS) necrotizing fasciitis causes exhaustion of the immune system, making these patients more susceptible for late secondary infections.MethodsA retrospective study was conducted of all patients with necrotizing fasciitis between 2002 and 2016. Patients with necroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Of all NSTIs, necrotizing fasciitis is the most well known and most common NSTI; other NSTIs are myonecrosis and necrotizing cellulitis [1]. Mortality and amputation rates for NSTI are considered high, with described mortality rates varying between 6 and 33% [2][3][4][5]. Factors such as advanced age, female sex, multiple comorbidities, and sepsis upon presentation have previously been linked to increased mortality rates [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all NSTIs, necrotizing fasciitis is the most well known and most common NSTI; other NSTIs are myonecrosis and necrotizing cellulitis [1]. Mortality and amputation rates for NSTI are considered high, with described mortality rates varying between 6 and 33% [2][3][4][5]. Factors such as advanced age, female sex, multiple comorbidities, and sepsis upon presentation have previously been linked to increased mortality rates [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality and amputation rates for NSTI are considered high, with described mortality rates varying between 6 and 33% [2][3][4][5]. Factors such as advanced age, female sex, multiple comorbidities, and sepsis upon presentation have previously been linked to increased mortality rates [2,5,6]. The bacteria causing NSTI can spread rapidly along the fascial planes; therefore, the saying "time is fascia" seems suitable.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review demonstrated a complication rate of 55–59% in patients [ 1 , 2 , 12 , 13 ], with the same risk factors for mortality: advancing age, multiple comorbidities, sepsis on admission, and signs of circulatory shock [ 1 , 36 , 37 ]. The percentage of complications in our study was in agreement with that in the literature, as was our mortality rate of 21.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Type I is polymicrobial and generally consists of various species of gram-positive cocci, gram-negative rods and anaerobes (2,10). Type II is monomicrobial with GAS being the most common microbe found (39,42). Recently an attempt was made to categorize specific strains of bacteria in their presentation, as Type III consists of more rare isolated 3) symptoms upon presentation.…”
Section: Causes Of Variation In Presentationmentioning
confidence: 99%
“…Studies were identified using the articles previously screened for our own meta-analysis ( 9) and was updated using the same search strategy, furthermore studies were identified from two previous systematic reviews on NSTIs. (39,43,44). Systemic toxicity of polymicrobial infections is most commonly dependent on the mechanism of microbial synergy and not necessarily on toxins.…”
Section: Causes Of Variation In Presentationmentioning
confidence: 99%